Comparison of the efficacy and safety of using 0.01% versus 0.03% bimatoprost for the treatment of eyebrow hypotrichosis: A randomized, double‐blind, split‐face, comparative study. (17th July 2019) - Suchonwanit, Poonkiat; Harnchoowong, Sarawin; Chanasumon, Nongsak; Sriphojanart, Tueboon
Abstract: Background: Previous studies have proven the efficacy and safety of 0.01% and 0.03% bimatoprost for the treatment of eyebrow hypotrichosis; however, there is no comparison study between both concentrations. Aims: To compare the efficacy and safety between 0.01% and 0.03% bimatoprost for the treatment of eyebrow hypotrichosis. Patients/Methods: This prospective, randomized, double‐blind, split‐face clinical study was conducted in 30 patients with eyebrow hypotrichosis. Each side of eyebrow of individual patients was randomly assigned for 0.01% and 0.03% bimatoprost, applied on each eyebrow once daily. Eyebrow density, diameter, the Global Eyebrow Assessment scale, 7‐point rating scale, and patient satisfaction were evaluated. Side effects were also recorded. Results: Both 0.01% and 0.03% bimatoprost significantly improved eyebrow density and diameter ( P  < .05), although there were no statistically significant differences in changes in eyebrow density and diameter from baseline between both concentrations ( P  = .96 and .84, respectively). Additionally, patients significantly preferred 0.03% bimatoprost in terms of clinical improvement and satisfaction ( P  = .04 and .003, respectively). Conclusions: Both 0.01% and 0.03% bimatoprost are effective and safe for the treatment of eyebrow hypotrichosis. Bimatoprost 0.03% is superior to its 0.01% counterpart, albeit without statistical significance.